Pengaruh Father Involvement Terhadap Career Adaptability pada Remaja di MAN 1 Padang - Lathifah Mahfudzah; Murisal; Dewi Fitriana (STAI AL-AMIN, 2026)
Career readiness during adolescence is a crucial issue in developmental psychology, as this stage requires individuals to adapt to various future career demands and choices. One of the psychological resources that plays an important role in career readiness is career adaptability, which refers to an individual’s ability to plan, control, explore, and develop confidence in career-related decisions. Family factors, particularly father involvement, are believed to contribute significantly to the development of adolescents’ career adaptability. This study aims to examine the level of father involvement, the level of career adaptability, and the effect of father involvement on career adaptability among adolescents at MAN 1 Padang. This research employed a quantitative approach with a causal-comparative design. The participants consisted of 269 students of MAN 1 Padang selected using purposive sampling. Data were collected using the Father Involvement Scale and the Career Adaptability Scale (CAAS). Data analysis was conducted using descriptive statistics and simple linear regression analysis. The results indicated that adolescents’ career adaptability was predominantly in the high category (83.8%), while father involvement was also mostly in the high category (57.7%). Regression analysis revealed that father involvement had a positive and significant effect on career adaptability (p < 0.05), with a contribution of 12.8%. These findings suggest that father involvement plays an important role as a protective factor in the development of adolescents’ career adaptability.